Pengembangan Bahan Ajar Komik Berbasis Flipbook untuk Meningkatkan Keterampilan Proses Sains Siswa Kelas V SD Negeri 2 Banda Aceh - Eka Yulianti; Sariakin Sariakin; Siti Mayang Sari (Jurnal Ragam Pengabdian, 2026)
This study aims to develop a comic-based flipbook teaching material and to examine its validity, practicality, and  effectiveness in improving elementary  school students’ science process skills. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 27 fifth-grade students of SD Negeri 2 Banda Aceh. Data were collected through observation, interviews, questionnaires, and learning outcome tests. The data were analyzed using descriptive quantitative and qualitative approaches. The results showed that the developed teaching material achieved a very high level of validity with an  average  score  of  96%,  categorized  as  highly  valid.  During  the implementation  stage,  the  use  of  the  comic-based  flipbook  increased students’ engagement and learning motivation. Furthermore, the evaluation results indicated an improvement in students’ learning outcomes, with the average score increasing from 57.4 in the pre-test to 82.4 in the post-test. In   conclusion,  the  comic-based  flipbook  teaching  material  is  valid, practical, and effective in enhancing students’ science process skills and can be used as an innovative alternative learning media in elementary